Research on optimal channel access method for distributed wireless network based on reliable multicast communication - Yizhu WANG; Zhou ZHANG; Piming MA; Baoquan REN (物联网学报)
To address the low spectrum utilization issue of the distributed network due to multi-user collision and channel time-varying nature, the distributed channel access problem for multicast communication was investigated.Based on the optimal stopping theory, a statistical model of distributed channel access under wireless multicasts was established, and an optimal distributed wireless channel access method under reliable multicast communication was proposed.Each source competes for the channel in a distributed manner, the winner source determines whether to access the shared channel by comparing the reliable multicast access rate with a pure threshold to complete the reliable multicast communication from the winner source to all the sinks.Theoretic optimality of the method was proved rigorously.A corresponding low-complexity algorithm was designed, which has a pure threshold structure and good engineering practicability.Numerical results show that the proposed channel access method can effectively improve the average throughput of the system.